Process Design and Optimization for Desulfurization of Diesel Using Ionic Liquids - Ben Salah, Haifa (2021)
A Master of Science thesis in Chemical Engineering by Haifa Ben Salah entitled, “Process Design and Optimization for Desulfurization of Diesel Using Ionic Liquids”, submitted in July 2021. Thesis advisors are Dr. Paul Nancarrow and Dr. Amani Al Othman. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).